Respuesta :

Answer:

see explanation

Step-by-step explanation:

Each term in the second factor is multiplied by each term in the first factor, that is

x²(2x² + 3x - 1) + 3x(2x² + 3x - 1) + 2(2x² + 3x - 1)

Distribute all 3 parenthesis

= 2[tex]x^{4}[/tex] + 3x³ - x² + 6x³ + 9x² - 3x + 4x² + 6x - 2

Collect like terms

= 2[tex]x^{4}[/tex] +9x³ + 12x² + 3x - 2

Answer:

2x^4+9x^3-7x^2-6x-2

Step-by-step explanation:

=2x^4+3x^3-x^2+6x^3+9x^2-3x-x^2-3x-2

Simplify

=2x^4+9x^3-7x^2-6x-2

ACCESS MORE